Locus branding as an element of territorial marketing of Caucasian Mineral Waters Resort towns - A. V. Baturov; V. F. Kshishnevskaya (Современная наука и инновации)
The city as a part of the socio-cultural space has its own uniqueness, which is expressed in the formation of its image. "Locus branding" (branding of the territory) is detailed by such concepts as "identity of the city", "identity of the territory", "cultural city code", "tourist city code". The mechanisms of branding the territory on the basis of "Locus branding" are considered. The factors that have a positive and negative impact on the formation of the tourist code of the resort city are identified. As a basis for the study of the locus branding of the resort city, it is proposed to consider the following factors affecting the coding of urban reality: natural, climatic; artistic works, historical events related to the city, architectural characteristics, symbolic connection with famous personalities. The mechanisms of forming a positive image of the city based on the emotional component are considered. Based on the conducted research, it is concluded that it is necessary to differentiate territorial marketing strategies for the formation and dissemination of a positive image of the resort city.